W kręgu polemik i dialogu. Literatura polska na Górnym Śląsku w latach 1922–1939 z perspektywy niemieckiej (PDF 11,91 MB) (Książnica Śląska, 2025)
The article discusses the subject of German-Polish relations in thefield of cultural cooperation in Upper Silesia in the years 1919–1939.The initial point for reflection is literary texts, essays and articlespublished in German-language magazines “Der Oberschlesier” and“Die Brücke – Most”. There were analyzed and critically assessedvarious statements by German historians, regionalists, writers, publishers and journalists, such as Karl Kaisig, Heinrich Koitz or August Scholtis, about poetry and prose written in Polish in UpperSilesia and about German-Polish cultural exchange. The analysisproves that magazines, on the one hand, served as bridge buildersin the process of agreement between two nations, on the other, theywere a tool of political propaganda focused on shaping the attitudes and opinions of their readers. It should be emphasized that onlya small group of German journalists and historians knew and read Polish literature. The summary reflection recalls the importantmonograph of the German literary scholar and writer Arno Lubos,“Geschichte der Literatur Schlesiens”.